Fabrication of mesa structural n‐type nanocrystalline‐FeSi2/p‐type Si heterojunction photodiodes by liftoff technique combined with photolithography. Issue 12 (18th November 2013) - Funasaki, Suguru; Promros, Nathaporn; Iwasaki, Ryuhei; Takahara, Motoki; Shaban, Mahmoud; Yoshitake, Tsuyoshi; Maeda, Yoshihito; Suzuki, Motofumi
Abstract Mesa structural n‐type nanocrystalline (NC) FeSi2/p‐type Si heterojunctions were fabricated by a liftoff technique combined with photolithography in order to improve the diode performance, particularly to reduce the parasitic capacitance. Their current‐voltage characteristics were experimentally studied in the dark and under illumination using a 1.31 μm laser at room temperature. Their junction capacitance density and leakage current density were evidently reduced as compared with those of the normal structural diodes. The mesa diode exhibits a good rectifying action with a rectification ratio of approximately three orders of magnitude at bias voltages of ±1 V. The photodetection was clearly observed owing to the suppression in the dark current. The estimated detectivity is 2.0 × 109 cm√Hz/W at zero bias, which is an order of magnitude larger than that of the normal structural diodes. This should be because the formation of interface states is reduced accompanied by the interface area reduction. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)